2019
DOI: 10.3390/biology8030052
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Myelinating Cultures as a Screen of Glycomolecules for CNS Repair

Abstract: In vitro cell-based assays have been fundamental in modern drug discovery and have led to the identification of novel therapeutics. We have developed complex mixed central nervous system (CNS) cultures, which recapitulate the normal process of myelination over time and allow the study of several parameters associated with CNS damage, both during development and after injury or disease. In particular, they have been used as a reliable screen to identify drug candidates that may promote (re)myelination and/or ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Most importantly, injecting a bacterial enzyme that degrades chondroitin sulfate promotes axonal regeneration in a variety of animal models (Alilain, Horn, Hu, Dick, & Silver, ; Bradbury et al, ; Carter et al, ; Rosenzweig et al, ), which represents a feasible approach for human therapy in the near future. In addition to chondroitin sulfate, heparan sulfate glycosaminoglycans also play important roles in neuronal development and axonal regeneration (Inatani et al, ; Lander, Stipp, & Ivins, ; McCanney et al, ; Poulain & Yost, ).…”
Section: Glycosaminoglycans In Axonal Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Most importantly, injecting a bacterial enzyme that degrades chondroitin sulfate promotes axonal regeneration in a variety of animal models (Alilain, Horn, Hu, Dick, & Silver, ; Bradbury et al, ; Carter et al, ; Rosenzweig et al, ), which represents a feasible approach for human therapy in the near future. In addition to chondroitin sulfate, heparan sulfate glycosaminoglycans also play important roles in neuronal development and axonal regeneration (Inatani et al, ; Lander, Stipp, & Ivins, ; McCanney et al, ; Poulain & Yost, ).…”
Section: Glycosaminoglycans In Axonal Regenerationmentioning
confidence: 99%
“…However, Barnett's laboratory has developed myelinating cultures (Sorensen, Moffat, Thomson, & Barnett, ) to test the role of heparan sulfate mimetics in remyelination and/or neurite outgrowth to study such aspects of SCIs (McCanney et al, ). Their results showed that N‐sulfated heparan sulfate mimetics promote myelination whereas O‐sulfated heparan sulfate mimetics do not affect myelination but promote neurite outgrowth (McCanney et al, ). Again, these findings demonstrated that different sulfation patterns in heparan sulfate play different roles for axonal regeneration.…”
Section: Glycosaminoglycans In Axonal Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that a panel of non-anticoagulant HS mimetics (mHep) generated by selective desulphation of commercial heparin have beneficial effects on CNS repair mechanisms [ 8 ]. Mixed neural cell cultures generated from dissociated embryonic rat spinal cords develop robust myelinated fibers separated by nodes of Ranvier (termed myelinating cultures) [ 9 , 10 ]. Using these cultures, we have demonstrated that low-sulphated mHeps (LS-mHeps) promote many facets of CNS repair [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using these cultures, we have demonstrated that low-sulphated mHeps (LS-mHeps) promote many facets of CNS repair [ 11 , 12 , 13 ]. We have used modifications of these cultures to mimic CNS injury, which has allowed us to examine factors that regulate the process of de novo myelination, remyelination and neurite outgrowth after injury [ 8 , 10 , 14 , 15 ]. We have previously shown that as many as 108 factors are released after CNS injury that may inhibit repair.…”
Section: Introductionmentioning
confidence: 99%